Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

Research on design and applications of multistable mechanical metamaterial structures with high fatigue resistance - Song Gao; Meiling Zhang; Lang Yu; Jinkui Chu; Jianwei Sun; Luquan Ren (Engineering Structures, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Mapping mollic epipedon thickness via ground-penetrating radar based on the combined method of Variational Mode Decomposition and Average Envelope Amplitude - Haipeng Lu; Xiangming Zhu; Wenjuan Zheng; Bin Zhang; Tianhao Wang; Yu Zhang; Meiling Fu; Enhua Ran (Soil and Tillage Research, 2026)

Artificial humic acid reshapes microbial C-N metabolism and nitrogen partition in microplastic-contaminated soils - Qihe Gao; Shuang Ai; Meiling Zhang; Yu Li; Yantong Li; Yadong Ma; Jiale Zhang; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

An NSGA-III–based predict–optimize–evaluate framework for low carbon land use optimization: A case study of the Yangtze River Delta - Menglin Yu; Jie Tao; Peng Zhang; Meiling Zhou; Beiying Huang; Jie Guo; Jialin Yi (Journal of Environmental Management, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Synergistic T cell and microbiome dysregulation in FOXP3-mediated immune enteritis: insights from multimodal omics - Meiling Jin; Cheng Jin; Shunlai Shang; Yuqing Gu; Peng Jin; Haibin Yu; Diangeng Li (Science China Life Sciences, 2026)

Emapalumab plus conventional therapy with or without ruxolitinib for pediatric hemophagocytic lymphohistiocytosis: a single center retrospective study - Meiling Liao; Li Xiao; Min Gu; Jie Yu (Immunologic Research, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Multi-scenario land use optimization towards carbon neutrality: An integrated predict-optimize-evaluate decision support framework - Menglin Yu; Tao Zhou; Jialin Yi; Wenxu Wang; Meiling Zhou; Jie Tao; Jie Guo (Journal of Cleaner Production, 2026)

Deciphering the mechanisms of phosphorus concentration in regulating nitrogen removal and autoaggregation of Pseudomonas stutzeri - Hanbo Zhao; Jie Huang; Meiling Tong; Yanghua Ou; Zhixuan Yu; Xiaowei Xu; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Spatiotemporal temperature variations induced by urban extreme heat events at the micro-scale - Huifang Li; Shuman Shen; Meiling Gao; Yu Wu; Zhihua Wang; Huanfeng Shen (Urban Climate, 2026)

Characterization of a myoinhibitory peptide and its role in neuroimmune regulation in Litopenaeus vannamei during Vibrio harveyi infection - Yongxiong Huang; Meiling Huang; XuYan Tan; Zhiqiang Zhang; Jia Cai; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2026)

Spatiotemporal changes of soil organic carbon in intensive croplands over three decades: Emerging role of farmland utilization shifts - Mingtao Xiang; Xiaojia Chen; Songchao Chen; Chunyan Wu; Meiling Sheng; Zhouqiao Ren; Wanzhu Ma; Ming Ming; Xunfei Deng; Yu Zhan (Soil and Tillage Research, 2025)

PPAR γ changing ALDH1A3 content to regulate lipid metabolism and inhibit lung cancer cell growth - Xinyuan Tian; Xiaoping Bai; Yunqi Han; Yu Ye; Meiling Peng; Hongwei Cui; Kai Li (Molecular Genetics and Genomics, 2025)

Deciphering macrophage heterogeneity and factors driving M2 polarization in lung adenocarcinoma through single-cell RNA sequencing - Meiling Sheng; Beiwei Yu; Qunzhi Wang; Yuanchao Xiao; Ming Ling; Xiaoming Wu (Apoptosis, 2025)

Fast prediction of indoor temperature distribution under spatiotemporal variation of solar radiation using equivalent surface heat sources and multimodal CNN - Ye Yuan; Junxi Gao; Meiling Li; Gang Liu; Yuebo Yu; Zixuan Yu; Hanyuan Zhang (Building and Environment, 2025)

Construction of fibromodulin and borneol-clacked phosphorus dendrimer nanoparticles to reduce inflammation and oxidative stress in BBB to nursing care and ischemic stroke therapy - Tian Li; Xin Jia; Meiling Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Comparison of efficacy and safety of dual orexin receptor antagonists lemborexant and daridorexant for the treatment of insomnia: a systematic review and meta-analysis - Ming Tang; Ziyi Shen; Peilu Yu; Meiling Yu; Xiaoqiong Tong; Guohui Jiang (Psychopharmacology, 2025)

Arthrospira platensis polysaccharide alleviates inflammation induced by PRV in RAW264.7 cells and mice via the regulation of LncRNA Dhx35/mmu-miR-185-3p/IL-17RA - Shouli Yi; Xiaodong Xie; Xiaoli Yu; Min Tang; Duong Thi Toan; Meiling Yu; Mixia Cao; Tingjun Hu (Algal Research, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Divergent mitigation mechanisms of soil antibiotic resistance genes by biochar from different agricultural wastes - Yu Yao; Peiyang Yang; Bin Wang; Qiao Xu; Fanhao Song; Yabo Wang; Yingdong Zhao; Lei Guo; Xiaozhi Wang; Meiling Xu (Environmental Pollution, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Expanding the electrochemical stable window of water through propylene carbonate addition for aqueous-based energy storage devices - Meiling Tang; Yu Meng; Yibing Yang; Shuilin Wu (Chemical Engineering Journal, 2025)

A mini-review on polyvinyl alcohol/lignin (nano)composites: Preparation, applications and perspectives - Meiling Han; Yu Zhang; Ying Zhang; Qing Ye; Mika Sillanpää; Xinli Zhu; Weijun Yang (Sustainable Chemistry and Pharmacy, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

Postglacial ocean methane release from the northern South China Sea - Mengyuan Wang; Xinyi Chen; Yu Liao; Lina Qin; Meiling Man; Guodong Jia; Ming Su (Quaternary Science Reviews, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

Enhanced oxygen anions generation on Bi2S3/Sb2S3 heterostructure by visible light for trace H2S detection at room temperature - Meiling Yu; Jiayu Li; Dongmin Yin; Zhenze Zhou; Chenda Wei; You Wang; Juanyuan Hao (Journal of Hazardous Materials, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

The immune function of heme oxygenase-1 (HO-1) from Nile tilapia (Oreochromis niloticus) in response to bacterial infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Adsorption Performance of Chitosan and Glutaraldehyde Modified Biochars for Trivalent Antimony in Acidic Wastewater - Huifang Lei; Nora F. Y. Tam; Xinhua Geng; Meiling Zhong; Xiaolan Lao; Xiaotong Su; Xuexia Huang; Lezhang Wei; Yu Liu; Qihang Wu; Ying-heng Fei; Dinggui Luo; et al. (Water, Air, & Soil Pollution, 2024)

Identification and functional characterization of interleukin-22 (IL-22) in orange-spotted grouper (Epinephelus coioides) - Dapeng Yu; Guanjian Yang; Jingyi Mo; Meiling Zhang; Hongli Xia; Zhen Gan; Yishan Lu (Fish & Shellfish Immunology, 2024)

Evaluation of magnetic calcium silicate hydrate derived from halloysite clay for efficient phosphate capture - Debin Jiang; Xue Long; Meiling Xiang; Xiantian Gan; Qinghong Pu; Yu Chen; Ning Qi; Xiaoping Wang (Journal of Environmental Chemical Engineering, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Apolipoprotein Eb (On-ApoEb) protects Oreochromis niloticus against Streptococcus agalactiae infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Impacts of shipyard oil leakage on the PAHs and PCBs occurrence in Xiangshan Bay, China - Yi Luo; Ganghui Tong; Qingbin Song; Peiran Tao; Meng Jin; Nitao Gu; Meiling Zheng; Xinwei Yu; Xubiao Yu (Marine Environmental Research, 2023)

Development and evaluation of diffusive gradients in thin-films technique with a novel titanium peroxide binding gel for in situ measurement of Tl in natural waters and sediments - Hongmei Deng; Meiling Liu; Zhaodong Liu; Minhua Su; Yue Gao; Danxing Yang; Yuxuan Liu; Liang Ma; Zhiqiang Yu; Tangfu Xiao; Jun Luo (Journal of Hazardous Materials, 2023)

Baicalein ameliorates polymyxin B-induced acute renal injury by inhibiting ferroptosis via regulation of SIRT1/p53 acetylation - Meiling Yu; Hongyu Li; Boying Wang; Zhenxiang Wu; Sheng Wu; Guojun Jiang; Huaxue Wang; Yingying Huang (Chemico-Biological Interactions, 2023)

Fine genetic mapping confers a major gene controlling leaf shape variation in watermelon - Ming Xu; Meiling Gao; Sikandar Amanullah; Yu Guo; Xiuping Bao; Yaru Duan; Xiujie Liu; Jixiu Liu; Yue Gao; Feishi Luan (Euphytica, 2023)

Design and synthesis of peptide-drug conjugates to double target EGFR - Xiaozhuo Tan; Meiling Le; Haiwen Wang; Bitao Huo; Tiantian Yu; Peng Huang; Tiangang Luan; Shijun Wen (Phytochemistry Letters, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53 - Hongyu Li; Boying Wang; Sheng Wu; Shuying Dong; Guojun Jiang; Yingying Huang; Xuhui Tong; Meiling Yu (Chemico-Biological Interactions, 2023)

Evaluation of the outdoor thermal environment for three typical urban forms in Nanjing, China - Ji-Yu Deng; Yueyang He; Meiling Dai (Building and Environment, 2023)

Molecular characterization and functional analysis of CD209E from Nile Tilapia (Oreochromis Niloticus) involved in immune response to bacterial infection - Yiqin Wu; Meiling Huang; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

Molecular mapping of candidate gene regulating fruit stripe trait in watermelon - Xiaoxue Liang; Meiling Gao; Sikandar Amanullah; Yu Guo; Hongguo Xu; Xiaosong Liu; Xiujie Liu; Jixiu Liu; Yue Gao; Chengzhi Yuan; Xuezheng Wang; Feishi Luan (Euphytica, 2022)

LncRNA Tug1 Contributes Post-stroke NLRP3 Inflammasome-Dependent Pyroptosis via miR-145a-5p/Tlr4 Axis - Meiling Yao; Ying Luo; Hongjie Li; Songjie Liao; Jian Yu (Molecular Neurobiology, 2022)

Effects of Microplastics on Higher Plants: A Review - Jia Li; Songguo Yu; Yufei Yu; Meiling Xu (Bulletin of Environmental Contamination and Toxicology, 2022)

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Mechanism of interactions between α-conotoxin RegIIA and carbohydrates at the human α3β4 nicotinic acetylcholine receptor - Meiling Zheng; Han-Shen Tae; Liang Xue; Tao Jiang; Rilei Yu (Marine Life Science & Technology, 2022)
Conotoxins are marine peptide toxins from marine cone snails. The α-conotoxin RegIIA can selectively act on human (h) α3β4 nicotinic acetylcholine receptor (nAChR), and is an important lead for drug development. The high-resolution cryo-electron microscopy structure of the α3β4 nAChR demonstrates several carbohydrates are located near the orthosteric binding sites, which may affect α-conotoxin binding. Oligosaccharide chains can modify the physical and chemical properties of proteins by changing the conformation, hydrophobicity, quality and size of the protein. The purpose of this study is to explore the effect of oligosaccharide chains on the binding modes and activities of RegIIA and its derivatives at hα3β4 nAChRs. Through computational simulations, we designed and synthesized RegIIA mutants at position 14 to explore the importance of residue H14 to the activity of the peptide. Molecular dynamics simulations suggest that the oligosaccharide chains affect the binding of RegIIA at the hα3β4 nAChR through direct interactions with H14 and by affecting the C-loop conformation of the binding sites. Electrophysiology studies on H14 analogues suggest that in addition to forming direct interactions with the carbohydrates, the residue might play an important role in maintaining the conformation of the peptide. Overall, this study further clarifies the structure–activity relationship of α-conotoxin RegIIA at the hα3β4 nAChR and, also provides important experimental and theoretical basis for the development of new peptide drugs.

Correction to: Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Clonidine Protects Against Neurotoxicity Induced by Sevoflurane Through NF-κB Signaling Inhibition and Proinflammatory Cytokine Release in Rats - Lian Guo; Yi Yu; Naixing Xin; Jing Sun; Yong Chen; Meiling Yu (Journal of Molecular Neuroscience, 2018)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)

Latitudinal patterns and influencing factors of soil humic carbon fractions from tropical to temperate forests - Li Xu; Chunyan Wang; Jianxing Zhu; Yang Gao; Meiling Li; Yuliang Lv; Guirui Yu; Nianpeng He (Journal of Geographical Sciences, 2018)

Identification and expression analysis of microRNAs during ovule development in rice (Oryza sativa) by deep sequencing - Ya Wu; Liyu Yang; Meiling Yu; Jianbo Wang (Plant Cell Reports, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Genome-wide transcriptome analysis of female-sterile rice ovule shed light on its abortive mechanism - Liyu Yang; Ya Wu; Meiling Yu; Bigang Mao; Bingran Zhao; Jianbo Wang (Planta, 2016)

A comparative analysis of the evolution, expression, and cis-regulatory element of polygalacturonase genes in grasses and dicots - Ying Liang; Youjian Yu; Jinlong Cui; Meiling Lyu; Liai Xu; Jiashu Cao (Functional & Integrative Genomics, 2016)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Identification and expression analysis of BoMF25, a novel polygalacturonase gene involved in pollen development of Brassica oleracea - Meiling Lyu; Ying Liang; Youjian Yu; Zhiming Ma; Limin Song; Xiaoyan Yue; Jiashu Cao (Plant Reproduction, 2015)

Comparison of Multi-Slice Computed Tomographic Angiography and Dual-Source Computed Tomographic Angiography in Resectability Evaluation of Pancreatic Carcinoma - Yongmei Yu; Meiling Guo; Xiangyu Han (Cell Biochemistry and Biophysics, 2014)

Application of 128 Slice 4D CT Whole Liver Perfusion Imaging in Hepatic Tumor - Meiling Guo; Yongmei Yu (Cell Biochemistry and Biophysics, 2014)

Molecular Cloning and Characterization of a Novel Polygalacturonase Gene, BcMF24, Involved in Pollen Development of Brassica campestris ssp. chinensis - Youjian Yu; Meiling Lv; Ying Liang; Xingpeng Xiong; Jiashu Cao (Plant Molecular Biology Reporter, 2014)

Resveratrol protects against arsenic trioxide-induced nephrotoxicity by facilitating arsenic metabolism and decreasing oxidative stress - Meiling Yu; Jiangdong Xue; Yijing Li; Weiqian Zhang; Dexing Ma; Lian Liu; Zhigang Zhang (Archives of Toxicology, 2013)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)

Phylogenetic relationships and estimation of divergence times among Sisoridae catfishes - MeiLing Yu; ShunPing He (Science China Life Sciences, 2012)

Structure and seasonal dynamics of bacterial communities in three urban rivers in China - Meiling Zhang; Na Yu; Liqiao Chen; Caihong Jiang; Yanjie Tao; Tian Zhang; Jun Chen; Di Xue (Aquatic Sciences, 2012)

Effects of temperature and organic and inorganic nutrients on the growth of Chattonella marina (Raphidophyceae) from the Daya Bay, South China Sea - Zhaohui Wang; Meiling Yuan; Yu Liang; Songhui Lu (Acta Oceanologica Sinica, 2011)